The Chlamydomonas bZIP transcription factor BLZ8 confers oxidative stress tolerance by inducing the carbon-concentrating mechanism. Issue 2 (10th December 2021) - Choi, Bae Young; Kim, Hanul; Shim, Donghwan; Jang, Sunghoon; Yamaoka, Yasuyo; Shin, Seungjun; Yamano, Takashi; Kajikawa, Masataka; Jin, EonSeon; Fukuzawa, Hideya; Lee, Youngsook
Abstract: Photosynthetic organisms are exposed to various environmental sources of oxidative stress. Land plants have diverse mechanisms to withstand oxidative stress, but how microalgae do so remains unclear. Here, we characterized the Chlamydomonas reinhardtii basic leucine zipper (bZIP) transcription factor BLZ8, which is highly induced by oxidative stress. Oxidative stress tolerance increased with increasing BLZ8 expression levels. BLZ8 regulated the expression of genes likely involved in the carbon-concentrating mechanism (CCM): HIGH-LIGHT ACTIVATED 3 ( HLA3 ), CARBONIC ANHYDRASE 7 ( CAH7 ), and CARBONIC ANHYDRASE 8 ( CAH8 ). BLZ8 expression increased the photosynthetic affinity for inorganic carbon under alkaline stress conditions, suggesting that BLZ8 induces the CCM. BLZ8 expression also increased the photosynthetic linear electron transfer rate, reducing the excitation pressure of the photosynthetic electron transport chain and in turn suppressing reactive oxygen species (ROS) production under oxidative stress conditions. A carbonic anhydrase inhibitor, ethoxzolamide, abolished the enhanced tolerance to alkaline stress conferred by BLZ8 overexpression. BLZ8 directly regulated the expression of the three target genes and required bZIP2 as a dimerization partner in activating CAH8 and HLA3 . Our results suggest that a CCM-mediated increase in the CO2 supply for photosynthesis is critical to minimize oxidative damage in microalgae, since slow gas diffusion in aqueous environments limits CO2 availability for photosynthesis, which can trigger ROS formation. Abstract : The Chlamydomonas bZIP transcription factor BLZ8 induces the carbon-concentrating mechanism to provide an electron sink pathway, reducing reactive oxygen species production under oxidative stress